Pn tomography and temperatures of Scandinavia - Watzak, Josh, author; Schutt, Derek, advisor; Stright, Lisa, committee member; Bangerth, Wolfgang, committee member (Colorado State University. Libraries, 2025)
We present a new high resolution tomographic study of the Scandinavian uppermost mantle from Pn traveltime tomography. This is accomplished by iteratively inverting for P-wave speeds using the Fast Marching Tomography package "FMTOMO", and using nearly 170,000 International Seismological Centre Pn picks as observational data. We map velocities to thermal structure derived from depth and temperature dependent metamorphic mineralogical variations of subcontinental lithospheric mantle. From resolution analysis, we achieve excellent raypath coverage and recovery of model structures at scales 2 ×2° or better. We present Vp and temperature results for the uppermost mantle at 60 and 70 km depths and find remarkable heterogeneity. In addressing the question of what sustains the enigmatic topography of the Scandes Mountains, we confirm the existence of low velocities beneath the southern Scandes and find elevated temperatures indicative of upper mantle dynamic support. Curiously, we also find similar high temperatures beneath the Lofoten Peninsula. However, for the northern Scandes, the dissimilar extent of elevated temperatures instead points towards shallower compensation of the topographic load, likely in the crust. We further validate the existence of a generally eastward thickening high density lower crustal layer from a pronounced low velocity ribbon we image beneath Finland. Our model's extent and resolution capabilities allow us to also identify thermal structures relating to the Cenozoic opening of the North Atlantic and Jurassic thermal doming in the North Sea.
Keywords: seismology; Pn tomography